Transformational vs. Transactional Leadership Style and Their Differential Impact on Employee Performance in SMEs: A Comparative Study in Banyumas Regency - Fatwa Zuhanea (JURNAL ILMIAH EDUNOMIKA, 2022)
This study investigates the differential impact of transformational and transactional leadership styles on employee performance in Small and Medium Enterprises (SMEs) in Banyumas Regency, Central Java, Indonesia. Despite the growing body of leadership research, comparative empirical evidence from SME contexts in developing economies remains limited, particularly regarding which leadership style yields superior performance outcomes. Anchored in the Full Range Leadership Model (FRLM), this research hypothesizes that both transformational and transactional leadership positively influence employee performance, with transformational leadership exerting a stronger effect. A quantitative survey design was employed with a sample of 145 employees from 28 SMEs across the trade, food production, and craft sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results revealed that transformational leadership (β = 0.421, p < 0.001) and transactional leadership (β = 0.287, p < 0.01) both significantly and positively affect employee performance, with transformational leadership demonstrating a substantially stronger effect. The model explained 61.3% of the variance in employee performance (R² = 0.613). These findings provide actionable insights for SME owners and HR practitioners in developing context-sensitive leadership training programs.